The entrepreneurial marketing of Trumpet Records. Issue 1 (11th July 2016) - Pane Haden, Stephanie; Kernek, Courtney; Toombs, Leslie
Abstract : Purpose: Definitions of entrepreneurial marketing (EM) abound. Unfortunately, a consensus definition and unified description of the construct still eludes scholars in the field, as multiple frameworks of EM have been proposed without agreement on which is the most valid and what variables are critical to an EM framework. The purpose of this paper is to provide a more comprehensive definition and framework of entrepreneurial marketing. Design/methodology/approach: Following a review of the extant literature pertaining to EM, as well as a brief review of the relevant literature regarding entrepreneurship in general, we identified a set of variables common and critical to this marketing approach. We then examined the historical case of Lillian McMurry, the founder of Trumpet Records, to provide a historical example of EM. Utilizing an abductive approach, we repeatedly analyzed the case alongside the salient literature. Findings: Through a methodology of systematic combining, we were able to advance a more comprehensive framework and definition of entrepreneurial marketing. Research limitations/implications: The primary limitation of most single case studies is the issue of generalizability. However, we accept the trade-off between limited generalizability and the conceptual understanding that this historical case provided. Originality/value: The proposal of a comprehensive definition and process framework of the relatively nascent construct of EM, supported by a historical case example, provides a solid base upon which future research can investigate the nuances of the variables critical to this emerging marketing approach.